2017
DOI: 10.1113/jp273825
|View full text |Cite
|
Sign up to set email alerts
|

Uteroplacental insufficiency reduces rat plasma leptin concentrations and alters placental leptin transporters: ameliorated with enhanced milk intake and nutrition

Abstract: Uteroplacental insufficiency reduces birth weight and adversely affects fetal organ development, increasing adult disease risk. Cross-fostering improves postnatal nutrition and restores these deficits. Mothers with growth-restricted pups have compromised milk production and composition; however, the impact cross-fostering has on milk production and composition is unknown. Plasma leptin concentrations peak during the completion of organogenesis, which occurs postnatally in rats. Leptin is transferred to the fet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 68 publications
(186 reference statements)
0
27
1
Order By: Relevance
“…The delta delta cycle of threshold (C t ) methodology was utilized to determine relative gene abundance compared to the male Control group. 23 Statistical analysis identified that Sdha was not different between treatments or sexes.…”
Section: Leptin Signalling Genesmentioning
confidence: 98%
See 3 more Smart Citations
“…The delta delta cycle of threshold (C t ) methodology was utilized to determine relative gene abundance compared to the male Control group. 23 Statistical analysis identified that Sdha was not different between treatments or sexes.…”
Section: Leptin Signalling Genesmentioning
confidence: 98%
“…Additional studies are also required to quantify protein expression in the kidney, especially considering leptin's clear ability to impair nephrogenesis. 28 23 thus maintaining a normal nephron endowment despite a poor postnatal environment. These data further highlight that nephrogenesis is delayed or extended in Restricted offspring.…”
Section: Uteroplacental Insufficiency Effects On Leptin Signallingmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin and SREBF‐1 are regulated by nutritional condition and play a central role in regulation of lipogenesis in the adipose tissue and the liver . Further, we have proposed that leptin is an important regulator of organogenesis . Although research has predominantly focused on how exposure to n‐6 FA in pregnancy can programme alterations to lipid regulation in offspring, fewer studies have investigated programming of other physiological systems.…”
Section: Effect Of Omega‐6 and Omega‐3 Fatty Acids In Fetal Programmingmentioning
confidence: 99%